Keberhasilan Kateter Foley Intraservikal Untuk Pematangan Serviks Pada Kehamilan ≥ 41 Minggu - Tendean, Hermie M.M.; Lumentut, Ariel W. (Jurnal Biomedik : JBM, 2020)
Abstract: This study aims to find out the succession number of intracervical foley catheter that used for cervical ripening in patients who has labor induction plan. Study involved 35 pregnant women with gestational age ³ 41 weeks, Bishop score < 6 that planned to undergo labor induction at Prof. Dr. R. D. Kandou General Hospital, Mana-do, in March to October 2020. Intracervical foley catheter applied to the patients for cervical ripening. Bishop score is performed before and after 24 hours uses of intracervical foley catheter or after experience foley catheter expulsion by itself. Succession of intracervical foley catheter assessed by Bishop score changes post expulsion of after 24 hours uses, with score ³ 6. Patients that never experience labor process post expulsion or foley catheter discharged performed labor induction with oxytocin drips. Average time of intracervical foley catheter installation is 12 hours. Average Bishop score before foley catheter installation 2,97 and Bishop score after expulsion or after 24 hours uses of intracervical foley catheter is 6,71. After t test has performed there is increasing of Bishop score after foley catheter installation (p < 0,001). In the amount of 82,86% patients that use intracervical foley catheter needed oxytocin drip for labor induction. In conclusion, intracervical foley catheter installation proves effectiveness for cervical ripening in case of Bishop score changes before application and after expulsion or 24 hours. Application with succession number of 77,14%.Key Words: intracervical foley catheter, cervical ripening, labor induction  Abstrak: Penelitian ini bertujuan untuk mengetahui angka keberhasilan kateter Foley intraservikal untuk mematangkan serviks pada pasien yang akan direncanakan induksi persalinan. Penelitian melibatkan 35 ibu hamil usia kehamilan ³ 41 minggu, skor Bishop < 6 yang akan direncanakan induksi persalinan di RSUP Prof. Dr. R. D. Kandou, Manado, sejak Maret sampai Oktober 2020. Pasien dipasang kateter Foley intraservikal untuk pematangan serviks. Dilakukan penilaian skor Bishop sebelum dan setelah 24 jam pemasangan kateter Foley atau setelah kateter Foley mengalami ekspulsi dengan sendirinya. Keberhasilan kateter Foley intraservikal dinilai dari perubahan skor Bishop post ekspulsi atau setelah 24 jam pemasangan, dengan nilai ³ 6. Pasien yang belum mengalami proses inpartu post ekspulsi atau pelepasan kateter Foley dilakukan induksi persalinan dengan menggunakan oksitosin drips. Lama rata-rata pemasangan kateter Foley adalah 12 jam. Nilai rata-rata skor Bishop sebelum pemasangan kateter Foley adalah 2,97 dan skor Bishop setelah ekspulsi atau setelah 24 jam pemasangan kateter Foley adalah 6,71. Setelah dilakukan uji t terdapat peningkatan skor Bishop setelah pemasangan kateter Foley (P < 0,001). Sebesar 82,86% pasien yang dipasang kateter Foley intraservikal membutuhkan oksitosin drips untuk induksi persalinan. Sebagai simpulan, Penggunaan kateter Foley intraservikal efektif untuk pematangan serviks dalam hal perubahan skor Bishop sebelum pemasangan dan setelah ekspulsi atau 24 jam pemasangan dengan angka keberhasilan sebesar 77,14%.Kata Kunci: Kateter Foley intraservikal, pematangan serviks, induksi persalinan.